Blockchain Implementation in Tourism Supply Chain to Ensure Transparency and Traceability of Environmental Impacts - Hugo Prasetyo Winotoatmojo; Gusneli; Muhammad Aga Sekamdo; Gredinov Sumanta Malsad; Firlie Lanovia Amir (Yayasan Inovasi Kemajuan Intelektual, 2022)
This study explores the implementation of blockchain technology in tourism supply chain management (TSC) to enhance transparency and traceability of environmental impacts. As the demand for sustainable tourism increases, the industry faces significant challenges in verifying green claims and tracking carbon footprints across a complex network of service providers. Using a systematic literature review and conceptual analysis, this study proposes a decentralized blockchain model capable of recording environmental data in real-time and immutable ways. The study demonstrates that blockchain can mitigate greenwashing by automating data verification through smart contracts. The study concludes that blockchain integration not only strengthens consumer trust but also provides an accountable framework for stakeholders to achieve global sustainability targets.